A sub-contratação nos serviços de manutenção: configuração da relação entre a grande empresa-cliente e as pequenas empresas fornecedoras - Mazzali, Leonel; Muñoz, Enrique Carlos Haro (Revista Gestão da Produção Operações e Sistemas, 2006)
This paper identifies and analyzes the main variables which configurate the interaction process between the small maintenance service companies and the major customer company. After the literature review, the following variables were selected: structure and policies of the customer company; procedures for identification, selection and evaluation of the suppliers; mechanisms of coordination, communication and supervision; technical knowledge degree, specialization and supplier agility; and the importance of the geographical closeness to the customer company. It is a descritive research, based on a survey carried out in 2005, through August and November. The research used a structured questionnaire together with an intentional sample composed by 28 customer companies and by 16 small supplier companies who are located in São Paulo city. Despite the customer-supplier relationship is not characterized as a partnership, the research detected some changes in the relationship, suggesting a closer perspective. Although the customer desires the specialization of the suppliers, the criteria applied to the selection and to the evaluation do not favor this profile. This research is unique, on one side, due to the presence of a supply chain surrounding the supplier and, on the other, distinct visions of the importance of the geographical closeness of the customer company, by the customer and supplier. Keyword: Maintenance, small business, partnership